Functional High-fidelity Prototype of a Student Meal Scheduling and Cafeteria Assistance System - dos Santos Valadares de Almeida, Gregório Cândido; Charles Nunes de Albuquerque, Monck; de Souza Cunha, Nataly (iSys - Journal of Information Systems, 2024)
At the Federal Institute of Bahia - Campus Seabra, many students request school meals via a form on Google Forms, the platform on which the Cafeteria depends to monitor requests, experiencing difficulty with manual processes and non-targeted functionalities. Thus, the objective of this work was the creation of a prototype to assist these demands and implement autonomy of the school. To do this, these steps were taken: define the app’s requirements and elements; technical training; building and testing, and professional validation. It was built a functional and intuitive high-fidelity system, ensuring a more comprehensive user experience and turning into reality a new solution for the Cafeteria’s meal requests.